Thermal and mechanical properties of prepacked concrete containing palm oil fuel ash - Vahedi, Abdolhamid (2015)
This research work outlines thermal and mechanical properties of prepacked concrete containing Palm Oil Fuel Ash (POFA). Prepacked aggregate concrete (PAC) is a special kind of concrete which is produced by first placing the coarse aggregates inside the molds followed by injection of grout by using pump or gravity method. The grout consists of sand, cement and water plus chemical and mineral admixtures. POFA is a mineral admixture which can be used as a supplementary cementitious material. This study determines the heat of hydration, heat transfer and mechanical properties of PAC with POFA replaced in different percentages of 0%, 10%, 20% and 30% by weight of cement. Along with thermal properties, properties of grout and strength of concrete were also investigated. The result obtained in this study demonstrated that the partial replacement of cement by POFA is advantageous and has very good potential to control the heat of hydration in prepacked concrete.